Implementasi Profetik Di Lembaga Pendidikan Menengah - Sirojudin, Didin; Al Ghozali, M Dzikrul Hakim (Universitas KH. A. Wahab Hasbullah, 2022)
Indonesia as a Pancasila State, all regulations are based on Pancasila. Meanwhile, in Islam, in an effort to improve the quality of education, it would be more appropriate if it was based on activities that had been exemplified by previous prophets and apostles, this is what is called prophetic education. Secondary education in Indonesia, both SMA, MA, SMK, and MAK accepts students between the ages of 15 – 18/19 years. They are in adolescence which is a period of transition from childhood to adulthood. This is an important period in the formation of identity. Judging from the type, this research is a qualitative research, data collection methods, namely: (1) observation (2) interviews (3) documentation. Furthermore, the data obtained and collected from field activities and qualitative analysis with data grouping techniques, then conclusions are drawn. In implementing prophetic in secondary education institutions must consider the psychological aspects of adolescent students, so that the implementation can run effectively in accordance with the reasoning and psychological power of students. Similarly, in determining approaches, strategies, and methods to be applied in the development of prophetic education in an educational institution. For the successful implementation of prophetic education in formal educational institutions, especially at the secondary education level, commitment and involvement of all elements of implementing education in schools or schools is required. madrasa as a unit in the system.